Exams at classroom have bidirectional effects on the long-term memory of an unrelated graphical task. (December 2018) - Lopes da Cunha, P.; Ramirez Butavand, D.; Chisari, L.; Ballarini, F.; Viola, H.
Abstract The influence of a given event on long-term memory formation of another one has been a relevant topic of study in the neuroscience field in recent years. Students at school learn contents which are usually tested in exam format. However, exam elevates the arousal state of the students acting as a mild stressor that could influence another memory formation ongoing process. Thus, in this study we examine in high school students the effect of exams on long-term retention of unrelated information, learned at different times before or after the exams. Our results show that exams are not innocuous and that they could improve or reduce the retention of temporarily associated content. These effects did not show gender differences. Our findings should alert teachers about the side effects of exams on the learning of other content within the same school day.